Length-weight and length-length relations for 21 fish species caught in Izmir Bay - Kara, Ali, biolog (Array, 2020)
This study exhibits relationships between length-weight and length-length for 21 fish species caught in Izmir Bay. Coefficients a and b for the length-weight relationships (LWRs) and length-length relationships (LLRs) were calculated with W=aLb formulae and as equations of TL=a+bFL and TL=a+bSL respectively. Equations of length-length for converting standard length and fork length into total length and vice versa were proven linear. The involved relationships were significantly interrelated (R2>0.942). Values b in the LWRs varied from 2.21 to 3.96 (mean ± SE: 3.15 ± 0.08). The student’s t-test showed that 87.9% of values b were significantly different from 3.